Visual Identity Design to Support Media Promotion for the Digital Business Study Program at the Indonesian University of Education - Muhammad Dzikri Ar Ridlo (Jurnal Impresi Indonesia, 2024)
In today's digital era, visual identity is an important point for creating a consistent visual identity. Especially as a promotional media which is an effective strategy in increasing student awareness in choosing study programs at higher education. Determining long-term choices that will have an impact on students' lives makes choosing a study program an important decision for prospective students. The student's future social life, profession, and level of personal satisfaction may be affected by this decision. Selecting a study program at a university is seen by prospective students as having the power to change the course of a person's life. Therefore, choosing a particular study program is a crucial choice. The visual identity attached to the product is very important for universities to facilitate media for the Indonesian Education University's Digital Business Study Program.